2020
DOI: 10.4037/ccn2020746
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Considerations in Adult Patients With Influenza-Induced ARDS

Abstract: Topic Acute respiratory distress syndrome is a complex respiratory disease that can be induced by influenza virus infection. Critical care providers are uniquely positioned to manage this pathological progression in adult patients through evidence-based practice. Clinical Relevance Influenza and subsequent acute respiratory distress syndrome are associated with extremely high morbidity and mortality in adult patients in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…[16] Severe infections can manifest as diffuse infiltration in lungs, refractory hypoxemia, and even acute respiratory distress syndrome. [17] A study on sepsis in infants reported that the detection rate of influenza virus was 7.8%. [18] JL and YL contributed equally to this article.…”
Section: Influenza Virusmentioning
confidence: 99%
“…[16] Severe infections can manifest as diffuse infiltration in lungs, refractory hypoxemia, and even acute respiratory distress syndrome. [17] A study on sepsis in infants reported that the detection rate of influenza virus was 7.8%. [18] JL and YL contributed equally to this article.…”
Section: Influenza Virusmentioning
confidence: 99%